TASTE MASKED ORODISPERSIBLE TABLETS: A HIGHLY PATIENT COMPLAINT DOSAGE FORM - Singh, Shivangi; Verma, Navneet (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Tablet is still most popular conventional dosage forms existing today, but the drawback of solid dosage forms is the difficulty in swallowing (dysphagia) or chewing in some patients particularly pediatric and geriatric patients. For this reason, orodispersible tablets (ODT) that can rapidly dissolve or disintegrate in the oral cavity have attracted a great deal of attention. The main objective of this review is to explore various methodologies for masking the taste of obnoxious drugs, applications, evaluation and also the recent trends in taste masking technologies when prepare a ODT. Methods: Pediatric and geriatric populations are the most sensitive to the bad taste of medicaments, thus in these cases patient compliance reduces. This reason is an initiative for the development of various taste masking technologies by which the characteristics of ODT is improved and good patient compliance is achieved. Results: ODTs have better patient acceptance and compliance and may offer improved biopharmaceutical properties, improved efficacy, and better safety compared with conventional oral dosage forms. Prescription ODT products initially were developed to overcome the difficulty in swallowing conventional tablets among pediatric, geriatric, and psychiatric patients with dysphagia. Conclusion: In this review, various techniques discussed which can help to overcome bitter taste of active pharmaceutical ingredients as well as largely improve the product preference among patients. It will also enhance the quality of the treatment provided to patients, especially children and older patients. Furthermore, various techniques could be combined to develop palatable and cost-effective ODTs. Keywords: Orodispersible tablet, Taste masking, Patient compliance.